COVID-19: PENGARUH LIVE STREAMING VIDEO PROMOTION DAN ELECTRONIC WORD OF MOUTH TERHADAP BUYING PURCHASING - Faradiba, Besse; Syarifuddin, Mustika (Economos : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to carefully examine the effect of live streaming video promotion and electronic word of mouth on buying purchasing during the large-scale social restrictions caused by the Covid-19 pandemic. The measurement of purchasing decisions in that study was carried out because there were still many sellers or marketers who were unfamiliar with live streaming video and electronic word of mouth in e-commerce in marketing their products. This academic research is typically expected to in common be a direct reference to invite sellers or producers to carefully choose to sell online through e-commerce because it is safer in practical terms of health. in that research method uses Multiple Linear Regression with convenience sampling or purposive sampling where the proportional quota is 50 respondents. The data analysis used is descriptive analysis to accurately describe the symptoms of the research results, while seeing the effect of live streaming video promotion and electronic word of mouth on buying purchasing (quantitative data) using multiple linear regression analysis tools. The direct results show that there is a simultaneous effect of live streaming video promotion and electronic word of mouth on buying purchasing, where the ANOVA test results show that the f-count value is greater than the f-table so that the hypothesis is accepted.